Comparision of different cell cultures for replication of infectious laryngotracheitis virus from chickens - Portz, Cristiana; Almeida, Laura Lopes de; Bianco Júnior, Alfredo; Reck, Herbert; Franco, Ana Cláudia; Canal, Cláudio Wageck (Acta Scientiae Veterinariae, 2018)
The propagation of infectious laryngotracheitis virus (ILTV) has been described using primary cell cultures derived from chicken embryo liver and kidney or embryonated eggs, but these cultures use Specific Pathogen Free (SPF) eggs that are time and cost expensive. Since cell line cultures are easier to maintain in laboratory conditions, the growth of ILTV was evaluated in five different cell cultures: chicken embryo related cells (CER), a cell hybrid derived from chicken embryo fibroblasts cells and BHK-21; Vero, from African green monkey kidney cells; HD11, a chicken macrophage cell line; CEC-32, an avian fibroblast cell line and a primary cell culture of chicken embryo fibroblasts (CEF). Cytophatic effect was observed until 96 hours following inoculation and the detection of the viral DNA was performed by PCR. The HD11 and CEC-32 cell lines did not support the virus growth but CEF and Vero, as already described were permissive cultures for propagation of ILTV. The results also showed that the CER cell line can be used for primary isolation and replication of ILTV.